2021
DOI: 10.3390/nu13020708
|View full text |Cite
|
Sign up to set email alerts
|

Advances and Future Directions in the Clinical Utility of Food Addiction

Abstract: The body of research examining the validity of food addiction and eating addiction far exceeds the research examining their clinical utility [...]

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…We examined sex differences in rates and the following correlates of FA in that sample: body mass index (BMI), frequency of loss of control over (LOC) eating, frequency of compensatory behaviors, severity of PTSD symptoms, severity of depression symptoms, suspected alcohol use disorder (AUD) severity, and frequency of alcohol use. Based on past research, we hypothesized that (1) women would have higher prevalence of positive FA status, compared to men; (2) individuals with positive FA status would have higher BMI than those without FA, regardless of sex; (3) there would be a significant interaction between FA status and sex, such that women with FA would report significantly higher frequency of LOC eating and compensatory behaviors compared to men and to women without FA; (4) there would be a significant interaction between FA status and sex, such that women with FA would report significantly higher PTSD symptom severity compared to men and women without FA; (5) individuals with positive FA status would report significantly higher depression severity, regardless of sex; (6) there would be no significant differences between individuals with and without FA in alcohol use.…”
Section: Study Aimsmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined sex differences in rates and the following correlates of FA in that sample: body mass index (BMI), frequency of loss of control over (LOC) eating, frequency of compensatory behaviors, severity of PTSD symptoms, severity of depression symptoms, suspected alcohol use disorder (AUD) severity, and frequency of alcohol use. Based on past research, we hypothesized that (1) women would have higher prevalence of positive FA status, compared to men; (2) individuals with positive FA status would have higher BMI than those without FA, regardless of sex; (3) there would be a significant interaction between FA status and sex, such that women with FA would report significantly higher frequency of LOC eating and compensatory behaviors compared to men and to women without FA; (4) there would be a significant interaction between FA status and sex, such that women with FA would report significantly higher PTSD symptom severity compared to men and women without FA; (5) individuals with positive FA status would report significantly higher depression severity, regardless of sex; (6) there would be no significant differences between individuals with and without FA in alcohol use.…”
Section: Study Aimsmentioning
confidence: 99%
“…FA remains a controversial construct: there are arguments that eating, not food itself, has addictive properties (similar to other behavioral addictions), hence making "eating addiction" a more useful construct than "food addiction" [3][4][5]. However, many researchers consider FA a useful construct in identifying individuals at risk for obesity and negative health outcomes related to maladaptive eating patterns, and its clinical utility is increasingly recognized [6]. Positive FA status has been linked to obesity [7] and the presence of eating disorders [8]; it is more prevalent than the DSM-5 eating disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Food addiction has been identified as a key barrier to the effectiveness of nutrition and weight loss interventions ( Cassin and Sockalingam, 2021 ; Schiestl et al, 2021 ), and is often comorbid with DSM-recognised eating disorders ( Gearhardt et al, 2014 ; Sanchez et al, 2022 ), which are highly prevalent among Australian adolescents ( Mitchison et al, 2020 ). As such, food addiction should be considered in the design, implementation and evaluation of nutrition interventions.…”
Section: Discussionmentioning
confidence: 99%
“…While not yet recognised as a disorder in the DSM, food addiction has some symptom overlap and comorbidity with recognised eating disorders, including binge eating disorder and anorexia nervosa (bulimic-purgative subtype) ( Gearhardt et al, 2014 ; Sanchez et al, 2022 ). Despite this overlap, food addiction is present in individuals who do not meet the criteria for other eating disorders ( Gearhardt et al, 2014 ), has demonstrated substantial clinical utility ( Cassin and Sockalingam, 2021 ), has unique treatment requirements ( Leary et al, 2021 ), and has been identified as a key barrier to the effectiveness of nutrition and weight loss interventions ( Cassin and Sockalingam, 2021 ; Schiestl et al, 2021 ). Food addiction is also associated with mental ill-health and reduced quality of life and individuals with lived experience describe a ‘cycle’ of distress to addictive eating to further distress ( Lacroix and von Ranson, 2020 ; Skinner et al, 2021 ; Van Ostrand, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Primarily, the app intervention emphasizes behavioural strategies aimed at withdrawal/abstinence from self‐identified problem foods, withdrawal/abstinence from snacking and excessive amounts at meals, and alternative non‐food related activities to displace discomfort 17,18 . Despite controversies over the construct of food addiction, there is growing interest in understanding how addictive‐like eating behaviours in adolescents impact weight loss trajectory in response to interventions 38‐43 . The components of this app intervention harness tools utilized in addiction medicine, such as cognitive behavioural therapy based skills training to assist with identifying and coping with triggers, establish behavioural coping strategies that are incompatible with over‐eating, increase non‐food sources of pleasure and reward, and bolstering social support for reducing addictive‐like eating behaviours.…”
Section: Discussionmentioning
confidence: 99%